Validation of thermal enhancement in micro channel heat using numerical analysis / Qamar Fairuz Zahmani - Qamar Fairuz , Zahmani (2018)
The cooling of electronic devices is essential to guarantee their functional performance and operational lifetime. Due to continued miniaturization and integration of transistors in packaged chips, the heat dissipation rate has surpassed the limits of classical air-cooled heat sinks. This has triggered a lot of research towards alternatives for high heat flux cooling. Liquid cooling with micro heat sinks is one of these candidate solutions. The first part of this thesis focusses on the validation of thermal enhancement in microchannel heat sink (MCHS) using numerical analysis. The single channel computational domain for the numerical simulation was adopted from MCHS. The basic geometry of the computational domain was obtained from the existing literature which related to the geometry of MCHS. With using experimental model demonstrated by M.R.Sohel, his experimental data was used as a reference to compare with the available analytical correlation and with numerical approached. The rate of heat transfer and flow of coolant of the MCHS in laminar or steady state condition were numerically investigated at a constant heat flux. Besides that, the study of the thermal and pressure lossï¿½s geometrical parameter effects will be carried out in this research. In the second part of this thesis, this there were an additional studied on the effect of aspect ratio and fluid flow rate in the MCHS, and the result obtained is discussed in this thesis. The overall result of the present work shows there is a close relationship between both the numerical and analytical data. Keywords: Microchannel, Validation, Heat Transfer. iv